Cellular uptake, intracellular distribution and degradation of Her2-targeting silk nanospheres - Florczak A (Dove Medical Press, 2019)
Anna Florczak,1,2 Andrzej Mackiewicz,1,2 Hanna Dams-Kozlowska1,21Department of Medical Biotechnology, Poznan University of Medical Sciences, Poznan 60-806, Poland; 2Department of Diagnostics and Cancer Immunology, Greater Poland Cancer Centre, Poznan 61-866, PolandCorrespondence: Hanna Dams-KozlowskaDepartment of Diagnostics and Cancer Immunology, Greater Poland Cancer Centre, 15 Garbary St., Poznan 61-866, PolandTel +48 61 885 0874Fax +48 61 852 8502Email hanna.dams-kozlowska@wco.plBackground: The development of nanocarrier technology has attracted great interest in the last decade. Biodegradable spheres made of functionalized silk have considerable potential to be used as drug delivery systems for cancer treatment. A targeting ligand displayed at the surface of a carrier, with a specific affinity towards a particular receptor, can further enhance the accumulation and uptake of nanoparticles at the site of a tumor.Materials and methods: The hybrid constructs were obtained by adding a Her2-binding peptide (H2.1) to MS1 and MS2 bioengineered silks based on the MaSp1 and MaSp2 proteins from N. clavipes, respectively. The H2.1MS1 and H2.1MS2 proteins were blended at a weight ratio of 8:2. Stable silk particles were formed by mixing a soluble protein with potassium phosphate using a micromixing technique. We used specific inhibitors of endocytosis to determine the cellular uptake pathway of the silk nanoparticles in human Her2-positive breast cancer cells. The subcellular distribution of silk particles was investigated by evaluating the signal colocalization with organelle-specific tracker. Moreover, lysosomal and exosomal inhibitors were implemented to evaluate their impact on the silk spheres behavior and degradation.Results: The functionalized spheres were specifically taken up by Her2-positive cancer cells. Silk particles facilitated the entry into cells through both the clathrin- and caveola-dependent pathways of endocytosis. Upon entering the cells, the particles accumulated in the lysosomes, where intracellular degradation occurred.Conclusions: The present study demonstrated directly that the lysosomal function was essential for silk-based carrier elimination. The degradation of the carrier is of great importance to develop an optimal drug delivery system.Keywords: silk spheres, endocytosis, nanoparticle trafficking, lysosomal degradation, targeted drug delivery, cancer therapy